Ferroptosis: Underlying mechanism and the crosstalk with other modes of neuronal death after intracerebral hemorrhage - Cao, Yuan; Xiao, Wenbiao; Liu, Shuzhen; Zeng, Yi (Frontiers in Cellular Neuroscience, 2023)
Intracerebral hemorrhage (ICH) is a serious cerebrovascular disease with high rates of morbidity, mortality, and disability. Optimal treatment of ICH is a major clinical challenge, as the underlying mechanisms remain unclear. Ferroptosis, a newly identified form of non-apoptotic programmed cell death, is characterized by the iron-induced accumulation of lipid reactive oxygen species (ROS), leading to intracellular oxidative stress. Lipid ROS causes damage to nucleic acids, proteins, and cell membranes, eventually resulting in ferroptosis. In the past 10 years, ferroptosis has resulted in plenty of discoveries and breakthroughs in cancer, neurodegeneration, and other diseases. Some studies have also reported that ferroptosis does occur after ICH in vitro and in vivo and contribute to neuronal death. However, the studies on ferroptosis following ICH are still in the preliminary stage. In this review, we will summarize the current evidence on the mechanism underlying ferroptosis after ICH. And review the traditional modes of neuronal death to identify the crosstalk with ferroptosis in ICH, including apoptosis, necroptosis, and autophagy. Additionally, we also aim to explore the promising therapeutic application of ferroptosis in cell death-based ICH.